Symmetries of center singularities of plane vector fields - Maksymenko, S.I. (Нелінійні коливання, 2010)
Let D² ⊂ R² be a closed unit 2-disk centered at the origin O ∈ R², and F be a smooth vector field such that O is a unique singular point of F and all other orbits of F are simple closed curves wrapping once around O. Thus topologically O is a «center» singularity. Let θ : D² \ O → (0, +∞ ) be the function associating with each z ≠ O its period with respect to F. In general, such a function can not be even continuously defined at O. Let also D⁺(F) — be the group of diffeomorphisms of D², which preserve orientation and leave invariant each orbit of F. It is proved that θ smoothly extends to all of D² if and only if the 1-jet of F at O is a «rotation», that is, j¹F(O) = −y(∂/∂x) + x(∂/∂y). Then D⁺(F) is homotopy equivalent to a circle.